Eksplorasi Karakter Melalui Pendekatan Visual Storytelling pada Film Pengabdi Setan Karya Joko Anwar - Qiyaadah Zahra; Dani Manesah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Film is an audio-visual media consisting of pieces of images put together, and has the ability to capture social and cultural reality, of course films are able to convey the messages contained therein (Alfathoni & Mahesah, 2020:2). The film Pengabdi Satan by Joko Anwar is a remake of the classic Indonesian film with the same title, which was released in 1980. The story centers on the Suwono family who live in an old and remote house. This family consists of Rini, mother, father, and Rini's younger brothers—Tony, Bondi, and Ian. One of the important elements that makes films have this impact is the visual storytelling technique which allows the audience to grasp the emotional and symbolic meaning of the story intuitively, without having to rely on words. The film Pengabdi Satan is a strong example of the use of visual storytelling and character exploration as the main elements in building a horror atmosphere and driving the narrative. In this film, visual storytelling is the main tool to create atmosphere and build tension slowly. Joko Anwar utilizes spatial layout, lighting and image composition to convey the sense of isolation, fear and helplessness experienced by the characters.